Case Report: The widening genetic and phenotypic spectrum of ultra-rare PDE4D-related acroscyphodysplasia - Morgul, Anna; Sharova, Margarita; Kenis, Vladimir; Orlova, Maria; Ryzhkova, Oxana; Markova, Tatiana (Frontiers in Medicine, 2025)
Acroscyphodysplasia (ASD) is an ultra-rare skeletal dysplasia characterized by severe brachydactyly, metaphyseal scaphoid knee deformities, growth retardation, and intellectual disability. To date, only seven cases of ASD have been reported, all associated with missense variants in the PDE4D gene. We report a 7-year-old girl with ASD features, including midface hypoplasia, severe growth retardation (−4.81 Shwachman–Diamond syndrome (SDS) height), progressive postnatal development of “cup-shaped” knee metaphyses, and unilateral humeral bowing, demonstrating mosaic growth plate involvement. Whole-genome sequencing revealed a novel PDE4D missense variant (c.934C>T, p. Leu312Phe) in the upstream conserved region 2 (UCR2) autoinhibitory domain, which is distinct from known acrodysostosis-associated variants. Expanding the clinical and radiological characteristics, as well as the mutation spectrum of PDE4D-related ASD, is crucial for understanding syndrome variability, aiding in earlier detection, and improving recurrence risk assessment.